Blood-based Biomarkers Used to Predict Disease Activity in Crohn's Disease and Ulcerative Colitis. Issue 5 (May 2015) - Burakoff, Robert; Pabby, Vikas; Onyewadume, Louisa; Odze, Robert; Adackapara, Cheryl; Wang, Wei; Friedman, Sonia; Hamilton, Matthew; Korzenik, Joshua; Levine, Jonathan; Makrauer, Frederick; Cheng, Changming; et al.
Abstract : Background: Identifying specific genes that are differentially expressed during inflammatory bowel disease flares may help stratify disease activity. The aim of this study was to identify panels of genes to be able to distinguish disease activity in Crohn's disease (CD) and ulcerative colitis (UC). Methods: Patients were grouped into categories based on disease and severity determined by histological grading. Whole blood was collected by PAXgene Blood RNA collection tubes, (PreAnalytiX) and gene expression analysis using messenger RNA was conducted. Logistic regression was performed on multiple combinations of common probe sets, and data were evaluated in terms of discrimination by computing the area under the receiving operator characteristic curve (ROC–AUC). Results: Nine inactive CD, 8 mild CD, 10 moderate-to-severe CD, 9 inactive UC, 8 mild UC, 10 moderate-to-severe UC, and 120 controls were hybridized to Affymetrix U133 Plus 2 microarrays. Panels of 6 individual genes discriminated the stages of disease activity: CD with mild severity ROC–AUC, 0.89 (95% confidence interval [CI], 0.84%–0.95%), CD with moderate-to-severe severity (ROC–AUC 0.98 [95% CI, 0.97–1.0]), UC with mild severity (ROC–AUC 0.92 [95% CI, 0.87–0.96]), and UC with moderate-to-severe severity (ROC–AUC 0.99 [95% CI, 0.97–1.0]). Validation by real-time reverse transcription–PCR confirmed the Affymetrix microarray data. Conclusions: The specific whole blood gene panels reliably distinguished CD and UC and determined the activity of disease, with high sensitivity and specificity in our cohorts of patients. This simple serological test has the potential to become a biomarker to determine the activity of disease. Abstract : Article first published online 2 April 2015.Supplemental Digital Content is Available in the Text.